Nanoemulsion Formulation and Antibacterial Activity of Nagasari (Mesua ferrea L.) Leaf Extract - Tuti Sri Suhesti; Eka Prasasti; Nisa Arifa Aldi (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Nagasari (Mesua ferrea L.) has antibacterial activity. Its active compounds are difficult to absorb. Nanoemulsions can enhance the absorption and solubility of these compounds. This study aims to determine the physical stability of a Nagasari extract nanoemulsion, as evaluated by its antibacterial activity. The nanoemulsion was prepared using VCO (1%) as the oil phase, Tween 80 (16%) as the surfactant, and PEG 400 as the cosurfactant, with variations of 1% (FI), 3% (FII), and 5% (FIII). The nanoemulsions were evaluated for their physical properties, solubility, organoleptic properties, pH, emulsion type, transmission percentage, particle size, polydispersity index, zeta potential, and stability. The most effective nanoemulsion was tested against B. subtilis. The results show that FI was stable during freeze-thaw testing. Its pH was 6.2 ± 0.15. FI was found to be an o/w emulsion-type with the following characteristics: transmission (94.23 ± 1.18%), polydispersity index (0.345 ± 0.051), particle size (103.07 nm), and zeta potential (-6.47 ± 2.20 mV). The stability and physical characteristics of the nanoemulsion are affected by variations in the concentration of PEG 400 as a co-surfactant. Antibacterial activity testing of the nanoemulsions resulted in an inhibition zone measurement of 19.15 mm against B. subtilis